-7(x+1)-13=26+3

Simple and best practice solution for -7(x+1)-13=26+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(x+1)-13=26+3 equation:


Simplifying
-7(x + 1) + -13 = 26 + 3

Reorder the terms:
-7(1 + x) + -13 = 26 + 3
(1 * -7 + x * -7) + -13 = 26 + 3
(-7 + -7x) + -13 = 26 + 3

Reorder the terms:
-7 + -13 + -7x = 26 + 3

Combine like terms: -7 + -13 = -20
-20 + -7x = 26 + 3

Combine like terms: 26 + 3 = 29
-20 + -7x = 29

Solving
-20 + -7x = 29

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '20' to each side of the equation.
-20 + 20 + -7x = 29 + 20

Combine like terms: -20 + 20 = 0
0 + -7x = 29 + 20
-7x = 29 + 20

Combine like terms: 29 + 20 = 49
-7x = 49

Divide each side by '-7'.
x = -7

Simplifying
x = -7

See similar equations:

| -32+28=4 | | y/15+6=y/6+12 | | -9=-6+3x | | 16x^4=y^2 | | 0=2(3x-5)+8(4x+7) | | -16t^2+3t+1.3=h(t) | | 12+m/4=3d-1/2 | | (2x-3)(x+3)=3 | | 4(a+3)=6(a-(5-a)) | | 6(3+v)+36v=13v | | 7r-8r=6 | | 5xy-3y-4=0 | | X-3/5+3/5=-x/2 | | -5t-26=18t | | -(100/-4) | | 3x+9=15forx | | 0=16t^2+44t-24 | | -3/4+7/3 | | 4=2a+37 | | 4x^2=12x-8 | | -4x^2-40x-106=0 | | -17=1+4n-7n | | g(x)=2f(x) | | -4/3-1 | | 6y+4=3(2y-10) | | 4/3-1 | | 2b-7b=5 | | 8x^2-13x-6x=0 | | x-ba=c+da | | a-bx=c+dx | | x+2(x+1)=122-3(x+2) | | -8(m+1)-m-12=-9(m+4)+16 |

Equations solver categories